Frailty, With or Without Cognitive Impairment, Is a Strong Predictor of Recurrent Falls in a US Population-Representative Sample of Older Adults. (15th March 2021) - Ge, Mei-Ling; Simonsick, Eleanor M; Dong, Bi-Rong; Kasper, Judith D; Xue, Qian-Li
Abstract: Background: Physical frailty and cognitive impairment have been separately associated with falls. The purpose of the study is to examine the associations of physical frailty and cognitive impairment separately and jointly with incident recurrent falls among older adults. Methods: The analysis included 6000 older adults in community or non-nursing home residential care settings who were at least 65 years old and participated in the National Health and Aging Trends Study. Frailty was assessed using the physical frailty phenotype; cognitive impairment was defined by bottom quintile of the clock-drawing test or immediate and delayed 10-word recall, or self/proxy-report of diagnosis of dementia, or AD8 score at least 2. The marginal means/rates models were used to analyze the associations of frailty and cognitive impairment with recurrent falls over 6 years of follow-up between 2011 and 2017. Results: Of the 6000 older adults, 1787 (29.8%) had cognitive impairment only, 334 (5.6%) had frailty only, 615 (10.3%) had both, and 3264 (54.4%) had neither. After adjusting for age, sex, race, education, living alone, obesity, disease burden, and mobility disability, those with frailty (with or without cognitive impairment) at baseline had higher rates of recurrent falls than those without cognitive impairment and frailty (frailty only: rate ratio [RR] = 1.31, 95% confidence interval [CI] = 1.18–1.44; both: RR = 1.28, 95% CI = 1.17–1.40). The association was marginally significant for those with cognitive impairment only (RR = 1.07, 95% CI = 1.00–1.13). Conclusions: Frailty and cognitive impairment were independently associated with recurrent falls in noninstitutionalized older adults. There was a lack of synergistic effect between frailty and cognitive impairment.